Ecosystem modification and network position impact insect-mediated contaminant fluxes from a mountaintop mining-impacted river network. (15th December 2021) - Naslund, Laura C.; Gerson, Jacqueline R.; Brooks, Alexander C.; Rosemond, Amy D.; Walters, David M.; Bernhardt, Emily S.
Abstract: Aquatic-terrestrial contaminant transport via emerging aquatic insects has been studied across contaminant classes and aquatic ecosystems, but few studies have quantified the magnitude of these insect-mediated contaminant fluxes, limiting our understanding of their drivers. Using a recent conceptual model, we identified watershed mining extent, settling ponds, and network position as potential drivers of selenium (Se) fluxes from a mountaintop coal mining-impacted river network. Mining extent drove insect Se concentration ( p  = 0.008, R 2  = 0.406), but ponding and network position were the principal drivers of Se flux through their impact on insect production. Se fluxes were 18 times higher from ponded, mined tributaries than from unponded ones and were comparable to fluxes from larger, productive mainstem sites. Thus, contaminant fluxes were highest in the river mainstem or below ponds, indicating that without considering controls on insect production, contaminant fluxes and their associated risks for predators like birds and bats can be misestimated. Graphical abstract: Image 1 Highlights: In a river draining mountaintop mines, Se is exported to land via aquatic insects. Mining extent, ponding, and network position were tested as controls on Se flux. Ponds increased Se fluxes to land by elevating insect production and Se content. Mainstem sites had higher Se fluxes than tributaries because of higher production. Drivers of production can be primary controls on insect-mediated contaminant flux.